2013
DOI: 10.3126/kumj.v10i2.7357
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Excision of A Fibroadenoma Breast: Trans Axillary Approach

Abstract: Benign breast lumps affect 10% of females in their lifetime. Surveillance, assurance, medications and surgical excision are options available to surgeons. Avoiding scars on the breast is an inherent feminine desire. Numerous minimal invasive approaches have evolved due to this concern. The time honoured circumareolar incisions camouflages the scar to a large extent, yet the incision still remains on the breast tissue and unfortunately the scar undergoes the same old sequelae as with any other scars both aesthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…In this study, 26 out of 36 patients (72.2%) (As we exclude the four open cases) had mild postoperative pain and 10 patients (27.8%) had moderate postoperative pain. This coincides with Agrawal et al, Aponte‐Rueda et al, and Adhikary et al al who reported insignificant pain with the use of paracetamol tablets for only two days postoperative.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this study, 26 out of 36 patients (72.2%) (As we exclude the four open cases) had mild postoperative pain and 10 patients (27.8%) had moderate postoperative pain. This coincides with Agrawal et al, Aponte‐Rueda et al, and Adhikary et al al who reported insignificant pain with the use of paracetamol tablets for only two days postoperative.…”
Section: Discussionsupporting
confidence: 89%
“…This agrees with the study done by Agrawal et al in which there was no skin burn reported. While Kitamura et al reported skin burn in one case, also Aponte‐Rueda et al, Adhikary et al reported the absence of intraoperative bleeding, wound infection nor axillary nerve injury at any of operated cases and most of the patients discharged on the second postoperative day. Also Lai et al reported that the mean hospital stay was 2.2 ± 0.4 days.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Novel clinical experiences describing new minimally invasive techniques with promising outcomes and cosmesis [4][5][6][7][8][9][10] predominantly mention transaxillary approaches. We present a novel endoscopic-assisted breast surgery for benign breast tumors through the inframammary fold.…”
Section: Introductionmentioning
confidence: 99%
“…However, minimally invasive methods including ultrasound guided vacuum-assisted biopsy have been described for breast lump removal [2, 3]. Also Endoscopic excision of breast fibroadenoma through the axilla which spared the breast from scar has also been described [4]. These sophisticated methods are not readily available in our setting probably due to the high cost of equipment and the expertise required.…”
Section: Introductionmentioning
confidence: 99%